2016
DOI: 10.1038/onc.2016.48
|View full text |Cite|
|
Sign up to set email alerts
|

A platform for interrogating cancer-associated p53 alleles

Abstract: p53 is the most frequently mutated gene in human cancer. Compelling evidence argues that full transformation involves loss of growth suppression encoded by wild-type p53 together with poorly understood oncogenic activity encoded by missense mutations. Furthermore, distinguishing disease alleles from natural polymorphisms is an important clinical challenge. To interrogate the genetic activity of human p53 variants, we leveraged the Drosophila model as an in vivo platform. We engineered strains that replace the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…4b), suggestive of impaired clearance. To test whether dp53, the Drosophila homolog of human p53 28, 29 , also affects SOD1 proteotoxicity, we crossed a stable dp53 RNAi strain to the mutant SOD1 flies, and observed that the reduction of dp53 significantly worsened the climbing deficits as well as increased the accumulation of mutant SOD1 protein (Fig. 4a,b), consistent with the role of p53 as a positive regulator of protein quality control.…”
Section: Resultssupporting
confidence: 53%
“…4b), suggestive of impaired clearance. To test whether dp53, the Drosophila homolog of human p53 28, 29 , also affects SOD1 proteotoxicity, we crossed a stable dp53 RNAi strain to the mutant SOD1 flies, and observed that the reduction of dp53 significantly worsened the climbing deficits as well as increased the accumulation of mutant SOD1 protein (Fig. 4a,b), consistent with the role of p53 as a positive regulator of protein quality control.…”
Section: Resultssupporting
confidence: 53%
“…Most of the mutations are located in the DNA binding domain, and very few are present in the translocation and tetramerization motifs. In the DNA binding domain, 32% of mutations are located on known hotspot residues, and the most frequent are the R248Q and R273C/H (12% and 7%, respectively) followed by H179R/D, H193R/Y, and S241Y (5% each), () [41].…”
Section: Serous-like Molecular Alterations In Ecsmentioning
confidence: 99%
“…Like mammalian counterparts, p53 genes in flies and worms act to specify adaptive responses to damage and promote genome stability (reviewed in ). As transcription factors, fly p53 and human p53 bind to identical sequence elements , but perhaps the most definitive evidence for functional conservation comes from studies on “humanized p53 fly strains,” where human p53 genes were used to rescue defective phenotypes caused by mutations in the fly counterpart . Upstream regulators in these networks are also conserved.…”
Section: Common Ancestry In the P53 Networkmentioning
confidence: 99%